TANGGUNG JAWAB HUKUM SECARA PERDATA PADA PERUSAHAAN TERHADAP PENCEMARAN DAN ATAU PERUSAKAN LINGKUNGAN MENURUT UNDANG-UNDANG NOMOR 32 TAHUN 2009 - Mig Irianto Legowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
The government has launched a sustainable development program, namely development carried out with an environmental perspective. In sustainable development, conditions must be met, namely, first, the existence of environmental sustainability and second, the fulfillment of the community's right to a clean and healthy environment. A process of development or production of a person or corporation. A corporation or company is a business entity or legal entity which in its production process is directly related to the environment. For this reason, it is likely that in the production process it can result in pollution or environmental damage. Environmental pollution and environmental destruction are caused by human actions that intentionally or unintentionally have exceeded the limits and even the environmental quality standards set, resulting in a decrease in environmental quality. , 04:21 WIB The Semarang City Government has three homeworks to do environmental damage. Pollution in Citarum tributaries. In April 2019, the Cibeet River in Taman Mekar Village, Pangkalan District, was filled with foamy waste. 32 of 2009 concerning Environmental Protection and Management (“PPLH Law”) Providing correct, accurate, open and timely information related to PPLH, Maintaining the sustainability of environmental functions, Complying with provisions on environmental quality standards and/or damage standard criteria environment. There are 3 ways to enforce corporate responsibility in environmental law, namely: Administrative Law Enforcement, Civil Law Enforcement, Criminal Law Enforcement, Civil liability discussion is classified separately. and how is the dispute resolution process for environmental pollution and or environmentaldamage carried out by the Company which has an impact on the loss of one of the disputing parties. This research uses normative legal research methods. Based on the description above, the conclusions, the results of the study are that: 1. Efforts that can be made in the settlement process are: Based on the provisions in Article 84 of Law Number 32 of 2009concerning Environmental Protection and Management, the company's responsibility for environmental pollution and or destruction environment, namely: civil liability (compensation), 2. Based on Law Number 32 of 2009 concerning Environmental Protection and Management, regulates efforts to resolve disputes both inside and outside the court, through other means, namely there are There are three ways of resolving disputes outside the court, namely negotiation, mediation and arbitration.